The Impact of Product Quality, Price, and Brand Image on the Purchase Decision of Acer Laptop Students in Bandar Lampung - Elvida, Nani; Ameraldo, Fedi; Ahluwalia, Larasati (Journals of Economics and Business, 2023)
This research aims to determine the influence of product quality, price and brand image on the decision to purchase Acer laptops among students in Bandar Lampung, both sequentially and simultaneously. The sampling method uses Purposive Sampling, the number of samples uses the Slovin Formula calculation with the formula ? = ? 1+?? 2 which produces 389 or rounded up to 390 respondents. Instrument testing uses Validity and Reliability Tests, data analysis methods use multiple linear regression analysis and coefficient of determination. The results of research on product quality, price and brand image partially have a positive and significant effect on purchasing decisions for Acer laptops in Bandar Lampung. The research results show that product quality, price and brand image simultaneously have a significant influence on the decision to purchase an Acer laptop in Bandar Lampung, while the coefficient of determination (R2) is 0.678. These results show that the Purchasing Decision variable can be influenced by Purchasing Decision (X1), Price (X2) and Brand Image (X3). Meanwhile, the remaining 32.2 contains other variables that are not in this study.